1979
DOI: 10.1002/mus.880020606
|View full text |Cite
|
Sign up to set email alerts
|

F waves in patients with hand wasting caused by a cervical rib and band

Abstract: In five patients with unilateral wasting of the hand muscles as a result of cervical rib and band, F waves were recorded from the hypothenar muscles following stimulation of the ulnar nerve at the wrist. Twelve healthy control subjects were also examined. F-wave latency was consistently increased in the affected hands of the patients, compared with results from the unaffected and control hands. This increase persisted after removal of the cervical band in four patients and was thought to be mainly due to degen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0
2

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 8 publications
0
16
0
2
Order By: Relevance
“…2,4,16 Direct needle stimulation of the C8 root and surface stimulation in the supraclavicular fossa have been used to measure conduction across the thoracic outlet. 9 Some authors have found an increase in F-wave latency in affected patients, 15,21 while others have reported that it did not add to the accuracy of the diagnosis. 12 Median SNAP has usually been found to be normal, contrasting with an altered ulnar SNAP at the wrist, indicating an ulnar or C8 lesion distal to the dorsal root ganglia.…”
Section: Discussionmentioning
confidence: 98%
“…2,4,16 Direct needle stimulation of the C8 root and surface stimulation in the supraclavicular fossa have been used to measure conduction across the thoracic outlet. 9 Some authors have found an increase in F-wave latency in affected patients, 15,21 while others have reported that it did not add to the accuracy of the diagnosis. 12 Median SNAP has usually been found to be normal, contrasting with an altered ulnar SNAP at the wrist, indicating an ulnar or C8 lesion distal to the dorsal root ganglia.…”
Section: Discussionmentioning
confidence: 98%
“…A reversible situation exists in conduction block due to cervical rib and band. Wulff and Gilliatt (1979) have shown improvement in F wave latency in one patient out of five following decompression of cervical rib and band. This was felt to be due to restored conduction of a few large motor axons which had been previously blocked.…”
Section: Discussionmentioning
confidence: 89%
“…Absence or prolongation of the ulnar F wave latencies is probably associated with significant compression of the neurovascular bundle at the thoracic outlet. 32 Abnormalities on needle EMG in patients with TOS have been reported by several aut h o r~.~~~~~~,~~,~~ Fibrillation potentials are usually sparse and found in the thenar and hypothenar muscles, particularly in patients with neurogenic TOS and atrophy of the small hand muscles. In the current series, only one patient had spontaneous activity (in the APB muscle).…”
Section: Discussionmentioning
confidence: 97%